Pengembangan Media Papan Tempel pada Materi Bagian Tumbuhan dan Fungsinya untuk Siswa Kelas IV Sekolah Dasar - Alfitra, Danda; Azizah, Diah Nur; Murniyati, Rahmi (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2023)
This research aims to develop learning media in the form of a sticky board called a sticky board for plant parts and their functions. This research aims to find out how the development process works and see student responses. This research is development research that adapts the ADDIE model developed by Lee and Owen. There are 5 main stages in this research consisting of: Analysis, Design, Development, Implementation and Evaluation. Product validation is carried out by a team of media experts and a team of material experts. After being validated, this multimedia was then tested on a small group of 5 class students. The results of the media expert validation analysis received a percentage of 94.44%. It is recommended that the sticky board media is very suitable for use as a learning medium in learning material about plant parts and their functions. Students can understand the parts of plants by linking the functions of class 4 elementary school to simple sentences in class I elementary school.